Life cycle cost of photovoltaic technologies in commercial buildings in Baja California, Mexico - Armendariz Lopez, J. F. (2016)
The appropriate use of photovoltaic technologies is essentially based on the identification of the available solar resource at the location in which they will be installed and the energy demand concerned. The purpose of this paper is to identify the geometric orientations that provide the best life-cycle cost for a multi-crystalline photovoltaic module, in order to supply electric energy for commercial buildings in three locations in Baja California, Mexico. The energy production of photovoltaic technologies was estimated on TRNSYS® according to a Typical Meteorological Year (TMY) simulated through spatial interpolation methods in Meteonorm®. Energy generation was compared in different orientations and inclinations of the photovoltaic array, its cost was calculated from the grid of the Federal Electricity Commission of Mexico. As a result, it was observed that in the city of Mexicali (hot-dry climate) the highest cost-benefit factor (3.17) and the shortest return on investment (13.02 years) was reached. The results showed that the multi-crystalline silicon photovoltaic cells represent a feasible investment option when installed in commercial buildings.